Measuring the impacts of seclusion on psychiatry inpatients and the effectiveness of a pilot single‐session post‐seclusion counselling intervention. (20th May 2013) - Whitecross, Fiona; Seeary, Amy; Lee, Stuart
Abstract Despite the accumulation of evidence demonstrating patients' accounts of trauma associated with seclusion, the use of evidence‐based post‐seclusion debriefing is not apparent in the published work. This study aimed to identify the impacts seclusion has on an individual using the Impact of Events – Revised (IES‐R), a standardized and widely used measure of trauma symptoms, and measure the effectiveness of a post‐seclusion counselling intervention in mitigating the experience of seclusion‐related trauma and reducing time spent in seclusion. The study design involved a comparison of the seclusion‐related trauma and time in seclusion that was experienced by consenting patients managed on the two inpatient wards of Alfred Psychiatry. To investigate the efficacy of post‐seclusion counselling to reduce event‐related trauma as well as the use of seclusion, a brief single‐session intervention was piloted comparing outcomes for patients treated on a ward implementing semistructured post‐seclusion counselling and patients treated on a ward continuing with post‐seclusion support as usual. A total of 31 patients consented to participate, with approximately 47% reporting trauma symptoms consistent with 'probable post‐traumatic stress disorder' (IES‐R total score, >33), although there was no difference in trauma experience between groups. Significantly fewer hours were spent in seclusion for patients treated on the ward piloting the post‐seclusion counselling intervention. Findings, therefore, highlight not only the potential for significant trauma stemming from a seclusion event, but also the capacity for the implementation of such interventions as post‐seclusion counselling to raise awareness of the need to minimize time spent in seclusion for patients.